Accounting Information System Analysis of Death Insurance Claims Payment at PT Taspen (PERSERO) Pematangsiantar Branch Office - Vitryani Tarigan; Marintan Saragih (Program Studi Akuntansi Universitas Simalungun, 2026)
This study aims to analyze the implementation and effectiveness of accounting information systems in the death insurance claim payment process at PT Taspen (Persero) Pematangsiantar Branch Office. The research method used is a qualitative approach with descriptive methods through data collection techniques including interviews, questionnaires, and documentation. The results show that the accounting information system has been implemented systematically from claim submission, document verification, data processing, to fund disbursement. The system is considered effective in improving efficiency, timeliness, and accuracy of information, although there are still obstacles such as incomplete documents affecting the process. Thus, the accounting information system plays an important role in supporting operational performance and service quality